2019
DOI: 10.1177/1028315319826320
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Higher Education and the Factors Influencing Student Decision-Making: The Experience of an Irish University

Abstract: Increasingly, universities have been engaging in transnational higher education (TNE), and such activity provides students with an additional study option. While much is already known about the TNE activities of universities in larger countries, such as Australia and the United Kingdom, very little is known about universities from smaller countries, such as Ireland. This article examines an Irish university with international branch campuses in Hong Kong, Singapore, and Sri Lanka. The results of a survey explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, confirmatory test analysis confirms that there exist some significant and underlying causal paths. This implies that the path/and or direction along which teaching, research, performance, learner attitude and internationalization are relevantly significant for the implication that the academic quality is definite and non-virtual with some inter-correlation inducing causalities as in studies of (Cheng., Wang., & Liu, 2014;Mukhwana et al, 2016;Nafukho et al, 2019;Ng'ethe, 2014 Chea., Tan& Huan2019;Nasirzadeh et al 2021;Nassa& Arora, 2021;Ndofirepi., Farinloye& Mogaji, 2020;Pitman et al 2020;Caeiro et al, 2020;Shahjahan et al , 2020;Henry et al 2020;Dowling., 2020;Kiraka, et al 2020;Okanović et al, 2021;Altakhaineh& Zibin2021;Zhang et al 2021;Calitz., Camilleri, 2021a;Cullen., & Kanyutu 2021;Feyen,2021;Shahjahan& Edwards2021).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…However, confirmatory test analysis confirms that there exist some significant and underlying causal paths. This implies that the path/and or direction along which teaching, research, performance, learner attitude and internationalization are relevantly significant for the implication that the academic quality is definite and non-virtual with some inter-correlation inducing causalities as in studies of (Cheng., Wang., & Liu, 2014;Mukhwana et al, 2016;Nafukho et al, 2019;Ng'ethe, 2014 Chea., Tan& Huan2019;Nasirzadeh et al 2021;Nassa& Arora, 2021;Ndofirepi., Farinloye& Mogaji, 2020;Pitman et al 2020;Caeiro et al, 2020;Shahjahan et al , 2020;Henry et al 2020;Dowling., 2020;Kiraka, et al 2020;Okanović et al, 2021;Altakhaineh& Zibin2021;Zhang et al 2021;Calitz., Camilleri, 2021a;Cullen., & Kanyutu 2021;Feyen,2021;Shahjahan& Edwards2021).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…and campus facilities (dormitories, sports complex, Wi-Fi, etc.) [6,18,20,24,[27][28][29]. Employment prospects and alumni success stories are also considered as one of the factors for IPTS selection [15,[17][18]22,30,34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employment prospects and alumni success stories are also considered as one of the factors for IPTS selection [15,[17][18]22,30,34]. In addition, the location of IPT and distance from home also play a vital role, especially post-Covid-19 [10,13,22,[28][29][31][32]34]. Finally, marketing includes advertising and promotion (TV, Internet, education carnival, etc) [6,29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the forerunners of academic research on student perceptions of DBs, Denny’s (2013) survey of 516 undergraduate students at The University of Auckland who could earn badges found that the majority of students (60%) felt earning badges was an enjoyable experience and preferred having the DBs in the course interface. Other studies showing positive responses toward badges and increased motivation in learning and class participation were conducted by Başal and Kaynak (2020), Cheng et al (2020) and Dowling-Hetherington and Glowatz (2017).…”
Section: What Have Scholars Learned Through Empirical Work About the ...mentioning
confidence: 99%